Asthma prevalence among high school students in East Jakarta, 2001, based on ISAAC questionnaire (Medical Journal of Indonesia, 2003)
The aim of this study was to assess asthma prevalence in children between 13-14 years of age in East Jakarta. This study is a cross sectional study which surveyed 2234 high school students between the ages of 13 and 14 years in East Jakarta in 2001 using the ISAAC questionnaire. Bronchial challenge test was applied by using methacholine substance to 186 students. Reports based on the ISAAC questionnaire indicate that 7.2% of teenage have had the wheezing experience, 4.1% have wheezing within the last 12 months, 1.8% have ever suffered severe asthma attack within the last 12 months, 3.3% have suffered wheezing after exercise, and 6.3% have got night cough while they were not suffering from cold. Prevalence of atopy diseases such as rhinitis and eczema were 14.2% and 3.9%, meanwhile rhinitis and eczema prevalence within the last 12 months according to this study were 10.6% and 2.9% respectively. Statistically, there is a significant correlation between wheezing symptom and atopy (p < 0.05). From indepth questionnaire, a significant value of kappa 0.84 related with wheezing within the last 12 months was found. Bronchial challenge test results indicate that sensitivity was 90%, specificity 83.58%, positive predictive value 68.12% and negative predictive value was 95.73%. Asthma prevalence in East Jakarta at 2001 based on ISAAC questionnaire was 8.9%, and cumulative prevalence 11.5%. The ISAAC questionnaire can be used to study asthma prevalence in children at multicenter in Indonesia. (Med J Indones 2003; 12: 178-86)